The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Explorations of Language Teaching and Learning With Computational Assistance
DOI: 10.4018/978-1-4666-1855-8.ch008
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Effects of Extended Online Thematic Listening Tasks on the Development of Listening Comprehension

Abstract: This study investigates the effects of employing extended online thematic listening tasks on the development of listening comprehension in an English course focusing on reading and writing skill development. To accomplish this aim, extended online thematic listening tasks were designed and implemented in English as a Foreign-Language (EFL) college level General English course. Pre- and post-tests were conducted to examine students’ gains in overall listening proficiency. Moreover, students’ mid-term and final … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…But when these problems happen in a web-based selflearning environment, they are more likely to generate learners' negative emotions and undesirable experiences due to limited scaffolding from others. Therefore, language teachers need to offer more guidance or scaffolding for learners to sustain learning in the webbased environment (Kung & Chuo, 2002;Lu, 2010;Sun et al, 2011). Previous literature has also noted the benefits of the support on learners' person knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But when these problems happen in a web-based selflearning environment, they are more likely to generate learners' negative emotions and undesirable experiences due to limited scaffolding from others. Therefore, language teachers need to offer more guidance or scaffolding for learners to sustain learning in the webbased environment (Kung & Chuo, 2002;Lu, 2010;Sun et al, 2011). Previous literature has also noted the benefits of the support on learners' person knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown mixed findings on this issue. For instance, Absalom and Rizz (2008) and Sun, Chang, and Yang (2011) have indicated that the learners who received online listening tasks could perform better in listening comprehension or retain more information than those who did not. However, in Chen and Zhang (2010), the learners who received an advanced online listening system did not make greater gains than those who received traditional listening instruction.…”
Section: Web-based Listeningmentioning
confidence: 99%
See 1 more Smart Citation